(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Both computational intelligence and pattern recognition depend on Brain lesion segmentation and classification. In this procedure, an effective algorithm was used to segment the lesion, and its characteristics, including LBP, were paired with the GLCM to extract the data from the picture. A morphologically based fuzzy C-means clustering technique (M-FCM) is suggested for clustering in segmentation. The severity of the information from the brain is then classified using CNN utilising the procedure used in the medical profession to detect brain lesions. The major goals of this procedure are to locate the malignant area on an MRI of the brain and to categorise the severity of that brain in order to increase process effectiveness.